Factores que determinan la demanda y su utilidad en la toma de decisiones financieras (Factors that determine the demand and its utility in the financial decision making) - Cortez Alejandro, Klender Aimer; Lazo Freymannt, Ricardo Guillermo; Rodríguez, M. (Facultad de Contaduría Pública y Administración U.A.N.L., 2008)
Abstract. The present document has like purpose of giving an explanation of which it is a function of demand and the practical utility of the estimation when relating it to qualitative variables of estimation of sales obtained from the experience of the experts. The form in how it sets out to carry out the previous thing is to raise the basic concepts firstly associate to the theory of the demand; these subjects are the factors that determine the demand, the displacements. In addition, the importance of the estimation of sales since they will serve as departure point for the adapted decision making of financial character in the organizations, by such reason considers is due to have special well-taken care of in its elaboration. Resumen. El presente documento tiene como finalidad dar una explicación de lo que es una función de demanda y la utilidad práctica de su estimación al relacionarla con variables cualitativas de estimación de ventas obtenidas a partir de la experiencia de los expertos. La forma en cómo se propone llevar a cabo lo anterior es plantear primeramente los conceptos básicos asociados a la teoría de la demanda; estos temas son los factores que determinan la demanda, los desplazamientos. Además, se plantea la importancia de los pronósticos de ventas ya que servirán de punto de partida para la adecuada toma de decisiones de carácter financiero en las organizaciones, por tal motivo se debe de tener especial cuidado en su elaboración.